Increasing Sugar Production and Its Alternatives and Availability of Plantation Land in Strengthening the National Economy - Rizerius Eko Hadisancoko (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this study is to find out the problem of the weakening of the Indonesian cane sugar industry which is unable to keep up with the rate of demand for Refined Crystal Sugar (GKR), especially for the food, beverage and pharmaceutical industries which has increased rapidly which has prompted the government to open up investment opportunities to build refined sugar factories using raw raw materials imported sugar. In addition, in order to explore alternative uses of raw sugar other than sugar cane, plantation management and trade mechanisms for domestic needs, as well as expansion of plantation land outside Java Island, in order to increase national sugar productivity.